Hepatitis C infection become a common issue among hemodialysis patients in a hemodialysis center Jakarta, Indonesia, and survival comparison of hemodialysis patients with hepatitis infection between two hemodialysis centers in Jakarta, Indonesia, and Penang, Malaysia - Diana Laila Ramatillah (Journal of Global Infectious Diseases, 2018)
Background: According to the Association of Nephrologist in Indonesia (Pernefri) recommendation, isolation and using special hemodialysis machines are not necessary for hemodialysis (HD) patients who have been infected by hepatitis C virus (HCV), while according to the Ministry of Health Malaysia recommendation, hepatitis C patients should be dialyzed in a separate room or a separate area with a fixed partition and dedicated machines. Aim: The aim of this study was to identify the correlation between the recommendation which had been followed by two HD centers in different countries and the impact of that on the hepatitis C infection issue. Methods: A cohort prospective and retrospective study was done in this research. The study included HD patients who were followed up for 9 months and who died in the last 5 years. Universal sampling was used to select the patients based on inclusion criteria. Results: There was a significant relationship between HCV during the first checkup and HCV during the second checkup during the 9-month follow-up of HD patients in a HD center, Jakarta, Indonesia. The total number of patients who had hepatitis C during the first and second checkups was also different in this HD center. Conclusion: Besides providing special HD rooms and machines for HD patients with hepatitis C, minimizing blood transfusion to the patients on HD is also important to reduce the chance for the patients to acquire hepatitis C and to increase the percentage of survival.